2017
DOI: 10.1080/02670836.2017.1309097
|View full text |Cite
|
Sign up to set email alerts
|

Hot ductility of high Al TWIP steels containing Nb and Nb-V

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. The hot ductility of B-Ti-Nb-high Al (1.5%Al) containing TWIP steels having Ti/N ratios mainly in excess of 3.4/1 was obtained. After soaking at 1250 o C, the tensile specimens were cooled at 12 or 60 o C/min to the test temperature and then strained to failure at 3X10 -3 /sec Ductility was always good (reduction of area>40%), independent of Ti/N ratio or cooling rate. The good ductility is du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Precipitation kinetics of AlN occurs during cooling while their growth rate and distribution are dependant on the thermal history e.g. slower cooling rate was found to enhance growth of particles [16]. In the current work, the majority of AlN particles were found along the grain boundaries in the form of rod and plate-like particles as presented in Fig.…”
Section: Resultssupporting
confidence: 49%
“…Precipitation kinetics of AlN occurs during cooling while their growth rate and distribution are dependant on the thermal history e.g. slower cooling rate was found to enhance growth of particles [16]. In the current work, the majority of AlN particles were found along the grain boundaries in the form of rod and plate-like particles as presented in Fig.…”
Section: Resultssupporting
confidence: 49%
“…The current authors [8] reported that adding 0.16%Al to HSLA steels enhances toughness considerably without impairing strength. A further study [9] revealed that the addition of 0.018%Nb is beneficial to improve the strength through grain size refinement and precipitation hardening [10,11]. Moreover, mechanical properties are affected by the processing conditions including the rolling condition that has a marked effect on properties, in which controlled rolling is known to further increase strength and toughness in comparison with hot rolling, but the effect of cooling rate after rolling must be taken care of [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in addition to the spectral lines from S, Mn, O, and Fe, there are also signals from Ce and La on the analyzed spectrograms (mischmetal was added during the melting process). The problem of non-metallic inclusions in high-manganese steels was analyzed in detail in works [28][29][30][31]. It is clear that that there is a relationship between numerous non-metallic inclusions and fracture behavior.…”
Section: Resultsmentioning
confidence: 99%